2021
DOI: 10.1016/j.eprac.2021.04.004
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 May Increase the Risk of Insulin Resistance in Adult Patients Without Diabetes: A 6-Month Prospective Study

Abstract: Objective During the coronavirus disease 2019 (COVID-19) pandemic, exploring insulin resistance and β-cell activity is important for understanding COVID-19-associated new-onset diabetes. This study aimed to assess insulin sensitivity and fasting insulin secretion in COVID-19 patients without diabetes on admission and at 3 and 6 months after discharge. Methods This 6-month prospective study assessed data from the records of 64 patients without diabetes diagnosed with COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 49 publications
3
44
1
Order By: Relevance
“…Thus, it is plausible that COVID-19 could create a perturbation in the glycometabolic complex system with resulting hyperglycemia and insulin resistance that can not only complicate the pathophysiology of pre-existing diabetes but also may lead to new-onset diabetes. Very recent studies showed that aberrant glycometabolic control and aggravated insulin resistant in COVID-19 patients without pre-existing diabetes persisted for at least 6 months after the infection [ 11 , 12 ]. Whether elevated glucose concentrations (in a non-diabetes range) or new-onset diabetes, is likely to remain permanent is not known at the present time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, it is plausible that COVID-19 could create a perturbation in the glycometabolic complex system with resulting hyperglycemia and insulin resistance that can not only complicate the pathophysiology of pre-existing diabetes but also may lead to new-onset diabetes. Very recent studies showed that aberrant glycometabolic control and aggravated insulin resistant in COVID-19 patients without pre-existing diabetes persisted for at least 6 months after the infection [ 11 , 12 ]. Whether elevated glucose concentrations (in a non-diabetes range) or new-onset diabetes, is likely to remain permanent is not known at the present time.…”
Section: Discussionmentioning
confidence: 99%
“…The SARS-CoV-2-induced down-regulation of ACE2 and the resulting increased Ang II may be a critical promoter of observed insulin resistance in COVID-19 [ 11 , 12 ] because increased levels of Ang II has been associated with deterioration of β-cell function [ 21 ]. In fact, in vivo studies showed that Ang II disrupts insulin-stimulated IRS-1/IRS-2-associated PI3-kinase pathway activities, thereby impairing GLUT-4 translocation into membrane of insulin-sensitive tissues such as muscle, liver and adipose tissue [ 22 , 23 ].…”
Section: Viral Entrance (Lateral Face 1)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, researchers could not eliminate BMI influencing carbohydrate metabolism, since the average BMI was higher than recommended. [64].…”
Section: Diabetesmentioning
confidence: 99%